Mangaji Tudang: AGH. As’ad Al-Bugisi’s Learning Method in Strengthening Wasathiyah Islam Based on Pesantren in Eastern Indonesia - Hamsir; Muhammad Alwi HS; Iin Parnisih; Khojir Khojir (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This article discusses mangaji tudang (Arabic: halaqah) initiated by AGH. As’ad at the pesantren of As’adiyah, which later developed and became a typical learning method for many pesantren in Eastern Indonesia. The phenomenon of mangaji tudang is used as a foothold in producing a pesantren-based model of Washatiyah. This article uses a type of literature processed based on the descriptive-analytical method concerning the socio-historical approach to related data to explore this goal. This article concludes that mangaji tudang not only brought students and the Bugis community to understand Islamic teachings but also created wasathiyah Islamic model. Thus, this article finds that mangaji tudang was initiated by AGH. As’ad is a learning method that integrates Islamic values into local culture, creating Wasathiyah Islamic model. Therefore, it is important to maintain, develop, and strengthen the existence of the mangaji tudang learning method to create a learning tradition that emphasizes Wasathiyah’s Islamic teachings